5-2(x-1)=3(2-x)+7

Simple and best practice solution for 5-2(x-1)=3(2-x)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(x-1)=3(2-x)+7 equation:


Simplifying
5 + -2(x + -1) = 3(2 + -1x) + 7

Reorder the terms:
5 + -2(-1 + x) = 3(2 + -1x) + 7
5 + (-1 * -2 + x * -2) = 3(2 + -1x) + 7
5 + (2 + -2x) = 3(2 + -1x) + 7

Combine like terms: 5 + 2 = 7
7 + -2x = 3(2 + -1x) + 7
7 + -2x = (2 * 3 + -1x * 3) + 7
7 + -2x = (6 + -3x) + 7

Reorder the terms:
7 + -2x = 6 + 7 + -3x

Combine like terms: 6 + 7 = 13
7 + -2x = 13 + -3x

Solving
7 + -2x = 13 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
7 + -2x + 3x = 13 + -3x + 3x

Combine like terms: -2x + 3x = 1x
7 + 1x = 13 + -3x + 3x

Combine like terms: -3x + 3x = 0
7 + 1x = 13 + 0
7 + 1x = 13

Add '-7' to each side of the equation.
7 + -7 + 1x = 13 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = 13 + -7
1x = 13 + -7

Combine like terms: 13 + -7 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| 7x^2-60x=0 | | 3-5x-4+7x=4x-2x+1 | | (3/11)/(2/3) | | Ligc=1.3 | | y=-0.90*50+113 | | 2x-3=3+2x | | y=-0.90*40+113 | | y=-0.90*30+113 | | sin(90)= | | log(4)+log(x)=2 | | y=-0.90*20+113 | | 7(p-5)=-91 | | 9w+3=-9 | | x-9.9=2.9 | | y=3x^3+3x^2-6x | | Inx^3-Inx=2 | | (g+6)*(g+7)= | | 3x-5=x+51 | | 5x-100=2x-13 | | (60+12)-(-7+4)= | | 5x-100=3x-13 | | -7p=8-7p | | 3-8z=-8z | | 15+37(7x)=70 | | 9+2d=2d | | H=3x^2+12x | | 5x^3+3=0 | | -35+5x=X+21 | | 5x-3-3=15 | | 5x-100=-134 | | 4x^5-100x=0 | | 3x=-113 |

Equations solver categories